Asymptotic normality of M-estimates in the classical nonlinear regression model - Ivanov, O. V.; Orlovs’kyi, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
Sufficient conditions are obtained for the asymptotic normality of M-estimates of the unknown parameters of nonlinear regression models with discrete time and independent identically distributed errors of observations.